Hydrophobic Deep Eutectic Solvent as Extractant Phase for Determining Six Carcinogenic Polycyclic Aromatic Hydrocarbons in Tea and Coffee Infusion Samples - Toledo-Neira, C; Toledo-Neira, C (Elsevier Inc., 2023)
In this work, an analytical methodology was developed for determining polycyclic aromatic hydrocarbons (PAHs) in tea and coffee samples. The new analytical methodology uses a hydrophobic deep eutectic solvent (DES), consisting of a thymol and lidocaine mixture, for the extraction of the analytes under dispersive liquid–liquid microextraction. The extraction procedure was optimized considering several variables (extraction phase composition, sample volume, vortexing and centrifugation time). Under optimum conditions, an using ultra-high-performance liquid chromatography with fluorescence detection as instrumental technique, the limits of detection were 39 and 53 ng·L−1 in tea and coffee samples, respectively. The precision expressed as relative standard deviation was better than 6.3 %. The relative recoveries were in the 60.7–85.2 % interval. The proposed method was successfully applied to the analysis of tea and coffee samples. The levels found for the six carcinogenic PAHs are between 10–45 µg·L−1 for tea infusions and 6–31 µg·L−1 for coffee infusions. The methodology is defined as an excellent green method with a score of 80 using the analytical Eco-scale. © 2023 Elsevier B.V.